The Islamic Business Ethics and Its Impact on the Performance of Small Micro Enterprises (SMEs) Actors in Serang Regency - Najmudin Najmudin; Ma'zumi Ma'zumi; Sujai Sujai (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to determine the impact of Islamic business ethics on the performance of Small Micro Enterprises (SMEs) Actors in the Serang Regency. The population in this study is Small Micro Enterprises (SMEs) Actors in Serang Regency, Banten Province. The respondents of this study were 70 SMEs actors in Serang Regency, Banten Province. The research method used is a quantitative method with data collection methods in the form of a questionnaire. The data were analyzed using instrument tests in the form of validity and reliability tests, classical assumption tests in the form of normality tests and heteroscedasticity tests, and hypothesis tests in the form of simple linear regression tests and correlation coefficient tests. The results of this study indicate that Islamic business ethics has a significant positive effect on the performance of Micro and Small Usama in Serang Regency, with a total contribution of 46 percent, while the rest is influenced by other variables not examined in this study.